Laporan Tentang Tanggapan Mahasiswa Pendidikan Bahasa Jepang Tingkat Pemula Terhadap Pertanyaan Tentang Hobi - Hermawan, Gede Satya (Sekolah Tinggi Bahasa Asing JIA, 2024)
This report shows the responses of beginner Japanese language learners to questions related to hobbies in the chokai shokyu (basic listening) class. The teaching material used is Marugoto Elementary Level 1 A2 -katsudou, with the topic of [watashi to Kazoku]. Two responses were found, namely appropriate and inappropriate. In the proper reactions, were 30 data divided into direct and indirect answers. There were also deficiencies in Japanese grammar but they did not reduce the information to be conveyed. This is understandable because the students are beginner Japanese language learners, they are only half semester learning the Japanese Language. Another thing related to the nouns used, the highest frequency is the noun geemu (o suru).